Brief Overview about Preoperative bowel preparation for gynecological oncology surgery (Journal of Pharmaceutical Negative Results, 2023)
Background: Gynecologycial Malignancies are specialized field of medicine that focuses on cancers of the female reproductive system, including ovarian cancer, uterine cancer, vaginal cancer, cervical cancer, and vulvar cancer. As specialists, they have extensive training in the diagnosis and treatment of these cancers. Bowel preparation has become an established practice before abdominal and gynecological surgeries. Most general surgeons would use both chemical bowel preparation and mechanical bowel preparation (MBP) before bowel surgery. In a survey of the practices of surgeons about the use of oral antibiotics in preoperative bowel preparation had the most disparate responses with 51% of the surgeons responding that the oral antibiotics were of doubtful or no use. However, despite their doubts, 75% of the surgeons routinely used oral antibiotic preparations, including 82% of those who questioned its usefulness